2007
DOI: 10.1021/ie061361b
|View full text |Cite
|
Sign up to set email alerts
|

Improved Two-Sided Tangent Plane Initialization and Two-Phase-Split Calculations

Abstract: The initialization procedure proposed by Michelsen for locating stationary points in the tangent plane distance function was applied to several cases considered as challenging in the literature concerning phase equilibrium calculations. For most of the systems studied in the literature, such a simple procedure is enough to detect the phase instability; thus it is unnecessary to resort to more robust, more elaborated, and more time-consuming initialization schemes. For the conditions and systems where problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Comparison of results presented in Table 2 with those presented in the literature [2,53] allows us to conclude that the algorithm employed to phase equilibrium calculations with phase stability analysis is reliable, since very well agreement was found between two sources. Besides, several systems presented by Cañas-Marin et al [48] were tested and the results obtained were identical to those reported by the authors (not included in the paper for brevity). Table 3 presents the systems used in this work and the related literature source.…”
Section: Phase Equilibrium Systemssupporting
confidence: 80%
See 3 more Smart Citations
“…Comparison of results presented in Table 2 with those presented in the literature [2,53] allows us to conclude that the algorithm employed to phase equilibrium calculations with phase stability analysis is reliable, since very well agreement was found between two sources. Besides, several systems presented by Cañas-Marin et al [48] were tested and the results obtained were identical to those reported by the authors (not included in the paper for brevity). Table 3 presents the systems used in this work and the related literature source.…”
Section: Phase Equilibrium Systemssupporting
confidence: 80%
“…As pointed out by Michelsen [47], usually, one of these initial estimations will converge to the trivial solution and the other one to the desired minimum for a specification in the heterogeneous region. However, as presented by Cañas-Marin et al [48] this strategy can be failed in solving phase stability problems for certain systems and specific conditions. Thus, as proposed by Cañas-Marin et al [48], the following convex interpolative strategy is used in this work:…”
Section: Phase Equilibrium Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase stability analysis, consisting in the minimization of the tangent plane distance (TPD) function [3] plays a key role in the initialization of multiphase flashes. While for two-phase flash calculation the stability is tested at most twice (Michelsen's two-side initialization [2]), in a multiphase context multiple initial guesses are required for phase stability [2,4,5]. If conventional variables are used (the minimum is sought in the compositional space) a nonlinear system of nc  (np À 1) equations must be solved.…”
Section: Introductionmentioning
confidence: 99%